70.4k views
0 votes
Multiply. (2x-1)(3x+5)

2 Answers

3 votes

Answer:

6x² + 7x - 5

Explanation:

FOIL method

Multiply the First terms

2x * 3x = 6x²

Then the Outer terms

2x * 5 = 10x

Inner terms

-1 * 3x = -3x

Last terms

-1 * 5 = -5

--------------------------

All together

6x² + 10x - 3x - 5

Combine like terms

6x² + 7x - 5

User Imran Rafiq Rather
by
5.8k points
0 votes

ANSWER

6x² + 7x - 5

Explanation:

(2x-1)(3x+5)

= 6x² + 10x - 3x - 5

= 6x² + 7x - 5

User Niklr
by
4.5k points